Decreased 5‐HT1A binding in mild Alzheimer's disease—A positron emission tomography study. Issue 7 (28th May 2022) - Mattsson, Patrik; Cselényi, Zsolt; Andrée, Bengt; Borg, Jacqueline; Nag, Sangram; Halldin, Christer; Farde, Lars
Abstract: Decreased 5‐HT1A receptor binding has been associated with Alzheimer's disease (AD) and interpreted as a consequence of neuron loss. The purpose of the present study was to compare [ 11 C]WAY100635 binding to the 5‐HT1A receptor in the hippocampus, entorhinal cortex, amygdala and pericalcarine cortex in mild AD patients and elderly controls. AD patients ( n = 7) and elderly control subjects ( n = 8) were examined with positron emission tomography (PET) and [ 11 C]WAY100635. PET data acquisition was performed with an ECAT EXACT HR system. Wavelet‐aided parametric images of nondisplaceable binding potential ( BP ND ) were generated using Logan's graphical analysis with cerebellum as the reference region. Correction for partial volume effects was performed with the Müller–Gärtner method. Regions of interest (ROIs) were applied to the individual parametric images, and the regional BP ND was calculated as the average parametric voxel value within each ROI. In addition to comparisons between subject groups, correlations between BP ND values and scores on the Mini‐Mental State Examination, Disability Assessment for Dementia (DAD), and Neuropsychiatric Inventory were expressed by Pearson correlation coefficients. Mean regional BP ND was lower in AD patients than in control subjects, and the difference was statistically significant for the hippocampus, entorhinal cortex, and amygdala. A statistically significant correlation was obtained between hippocampal BP ND values and DAD scores. The results of the present study corroborate and extend previous findings of decreased 5‐HT1A binding in AD and strengthen the support for 5‐HT1A receptor PET as a tool for the assessment of neurodegenerative changes in mild AD. Abstract : [ 11 C]WAY100635 binding was measured with positron emission tomography (PET) in mild Alzheimer's disease (AD) patients and elderly control subjects. The mean nondisplaceable binding potential was lower in the hippocampus, entorhinal cortex, and amygdala in AD patients than in controls, supporting 5‐HT1A receptor PET as a tool for the assessment of early neurodegenerative changes in AD.